2022
DOI: 10.30541/v55i4i-iipp.605-618
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rising Energy Prices on Consumer’s Welfare: A Case Study of Pakistan

Abstract: This work investigated the impact of higher energy prices on consumer’s welfare for the Pakistan from 1987 to 2012. The central objective of the study is to quantify the consumer welfare through Compensating Variation (CV) after estimating the demand elasticities by applying the Linear Almost Ideal Demand System (LA/AIDS) for main energy sources. Welfare change is also measured in four scenarios (two price shocks) for Pakistan in order to analyse the impact of energy price … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…For this reason, consumers' expenditure on energy products (electricity, gas, kerosene oil and firewood) has gradually decreased, leading to a reduction in the welfare loss for both rural and urban consumers. These results are consistent with Aziz et al (2016), who conclude that CV is positive (and consumer welfare falls) due to a rise in energy prices, especially in inflationary conditions.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…For this reason, consumers' expenditure on energy products (electricity, gas, kerosene oil and firewood) has gradually decreased, leading to a reduction in the welfare loss for both rural and urban consumers. These results are consistent with Aziz et al (2016), who conclude that CV is positive (and consumer welfare falls) due to a rise in energy prices, especially in inflationary conditions.…”
Section: Resultssupporting
confidence: 91%
“…Adagunodo (2013) employs an AIDS model to examine the effect of energy prices reform on consumer welfare in Nigeria. Aziz et al (2016) use the same approach (LA/AIDS) while investigating the impact of energy prices on consumer welfare in Pakistan.…”
Section: Aids Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The consumer price index had a positive long-run association so monetary policy affects inflation. Aziz et al (2016) identified the impact of higher energy prices on consumer welfare for Pakistan. The time-series data was used from 1987 t0 2012.…”
Section: Introductionmentioning
confidence: 99%
“…This study is different from previous studies on the research topic as it measures energy prices in domestic pump diesel prices and pump gasoline prices. While the previous studies have measured the energy prices on the basis of international crude oil prices per barrels and ignore the cost of government taxes, transportation cost, profits of the organization (Qasim et al, 2021;Iqbal et al, 2021;Aziz et al 2016;Saleem & Ahmad, 2015). The energy prices on the basis of international crude oil prices is not a good measure of domestic energy prices.…”
Section: Figure 2 Consumer Price Index(cpi)mentioning
confidence: 99%